Digital Preservation of Heterogeneous Data - Barateiro, J. (2009)
Digital preservation aims at maintaining digital objects and making data accessible over long periods of time. The emerging context of e-Science imposes new scenarios and new requirements for digital preservation. This paper presents the main issues, current solutions and prominent projects for digital preservation and e-Science data management. Finally, it presents the problem to be addressed, the solutions to explore, the proposed methodology and expected contributions of the associated PhD work.